An extended set of interaction primitives for multi-agent systems development - Tucat, Mariano (2005)
The research line reported here involves the improvement of the set of interaction primitives that we have developed [8, 2] for the implementation of multi-agent systems in dynamic and distributed environments. This interaction primitives have been implemented for allowing the creation of several independent multi-agent systems, where agents communicate with others just by knowing the other agents' names. The framework includes primitives for associating the arrival of a message with the automatic execution of a Prolog predicate, thus allowing event-based programming. It also allows the implementation of standard Agent Communication Languages, and provides tools for developing standard Agent Conversation Protocols. We will first describe briefly our framework and then we will propose some improvements for it.